THE RELATIONSHIP BETWEN AGE AND ORAL HEALTH BEHAVIOR AMONG INTEGRATED HEALTH POST CADRES IN SENDANGMULYO VILLAGE IN THE WORKING AREA OF KEDUNGMUNDU COMMUNITY HEALTH CENTER - Maulida, Alfina; Mifbakhuddin, Mifbakhuddin; Kusniati, Retno; Sholekhah, Nur Khamilatusy; Budiono, Budiono (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
ABSTRACT Background: Dental and oral health refers to the condition of a healthy oral cavity, which includes the health of the soft tissues and hard tissues of the teeth, so that an individual can eat, speak, and engage socially without being hindered by functionality and aesthetics, allowing individuals to lead a productive life both socially and financially. This study aims to determine the relationship between age and dental and oral health behaviors, which include levels of knowledge, attitudes, and practices, among posyandu cadres in Sendangmulyo Village, the working area of Kedungmundu Public Health Center.Method: This research uses observational analysis with a cross-sectional design and the sampling method is simple random sampling with a total sample size of 63 people. Statistical analysis uses the Chi-square test. Result: The results of the Chi-Square correlation statistical test showed a p-value of 0.005, indicating a relationship between age and dental and oral health behavior, which includes levels of knowledge, attitudes, and practices among posyandu cadres.Conclusion: It was concluded that there is a significant relationship between age and dental and oral health behavior, which includes levels of knowledge, attitudes, and practices, among the posyandu cadres in Sendangmulyo village, the working area of Kedungmundu Health Center.